Sedimentology and Basin Development of the Middle Miocene Succession in the Zurbatiya Area, Eastern Iraq - Omar, Maysoon; Al-Shamary, Thamer Abaas (Iraqi Journal of Science, 2018)
The present study is focused upon the sedimentology and basin development of the Jeribe and Fatha Formations by using the field observations and microfacies analysis. The area of study situated in the Zurbatiyah area to the south of the Shur sharin valley about 21 km northeast of Badrah city to the southeast of Baghdad. This area lies within the Zagros foreland basin, and located between the Zagros mountains at the northeastern and the Arabian shield at the southeastern. The studied succession which including the Jeribe and Fatha Formations were deposited within four associated facies for the Jeribe Formation and three for the Fatha Formation, as shown below: -Jeribe Formation includes dolomitized mudstone-wackstone (semi restricted); Milliolid wackestone-packstone (shallow open marine), Dolomitic packstone (lagoon).Fatha Formation includes pelecypods bioclastic wackestone-packestone (lagoon); peloidal bioclastic packstone (lagoon); massive gypsum (evaporitic lagoon); laminated gypsum (supratidal and evaporitic lagoon)The facies analysis for the studied succession showing two stages of deposition:- The first stage is represented the final transgression stage in the studied area. The fall sea level gradationally appeared by shallowing up-ward and more dolomitized upward from the middle part of the Jeribe Formation. The second stage the deposition was started when the first beds gypsum and anhydrite is appeared for the Fatha Formation refer to the restricted and supratidal environment. The uplifted of the eastern and northeastern parts of Iraq generate a tectonic depositional ridge to the west and northwestern resulted in the formation of restricted basins and regional regression in the Arabian plate.